TEMPO-SPATIAL DISTRIBUTION AND RELATED FUNCTIONINGS OF ROOT GLOMALIN AND GLOMALIN-RELATED SOIL PROTEIN IN A CITRUS RHIZOSPHERE - Qiang-Sheng Wu; Shuang Wang; Ming-Qin Cao; Ying-Ning Zou; Yan-Xing Yao (Journal of Animal and Plant Sciences, 2014)
Citrus trees in China are mostly cultivated in poor soils, where management of root and soil glomalin are of great significance. The tempo-spatial dynamics of root mycorrhizal colonization, glomalin, sucrose and glucose and soil organic carbon (SOC), total and easily-extractable glomalin-related soil protein (T-GRSP and EE-GRSP), and mean weight diameter (MWD, an indicator of aggregate stability) were studied in the rhizosphere of a 24-yr-old Citrus unshiu grafted on Poncirus trifoliata. In general, root mycorrhizal colonization, glomalin and GRSP reached maximal values in July and were higher in 0–15cm than in 15–30cm soil layer. Mycorrhizal colonization was positively correlated with T-GRSP and EE-GRSP but negatively with root glucose. There was a relatively low root glomalin concentration (0.047–0.278 mg g-1 DW) in citrus rhizosphere. A highly positive correlation of root glomalin and EE-GRSP was with root glucose and root sucrose, suggesting that a certain amount of GRSPs and root glomalin were partly from root glucose and sucrose. SOC but not two GRSP fractions were significantly positively correlated with MWD, and GRSP thus was not the main aggregate binding agent in the soils. In addition, SOC was highly positively correlated with root glomalin and without two GRSPs, resulting in higher contribution of root glomalin to SOC than GRSP. We conclude that root and soil glomalin exhibited highly tempo-spatial distribution patterns and did not contribute aggregate stability.
Keywords: Aggregate stability; Citrus; Glomalin; Glomalin-related soil protein; Mycorrhiza; Soil organic carbon